2020
DOI: 10.1016/j.clgc.2019.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Ureterectomy for Upper Tract Urothelial Carcinoma: A Systematic Review and Meta-analysis of Comparative Studies

Abstract: Radical nephroureterectomy (RNU) represents the standard of care for high-risk upper tract urothelial carcinoma (UTUC). In selected patients with ureteral UTUC, a conservative approach such as segmental ureterectomy (SU) can be considered. However, this therapeutic option remains controversial. The aim of this study was to perform a systematic review and meta-analysis of studies assessing the outcomes of SU versus RNU in patients with UTUC. Three search engines (Scopus, Embase, and Web of Science) were queried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Surgical excision and chemotherapy were also suitable for UTUC patients with bone metastasis, which was consistent with previous mainstream treatments for patients with primary tumors ( 17 , 33 , 34 ). In advanced UTUC, radical nephroureterectomy (RNU) still remains the standard of care ( 35 ). Alberto Martini et al ( 36 ) reported that neoadjuvant chemotherapy may be an option in patients with UTUC and bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision and chemotherapy were also suitable for UTUC patients with bone metastasis, which was consistent with previous mainstream treatments for patients with primary tumors ( 17 , 33 , 34 ). In advanced UTUC, radical nephroureterectomy (RNU) still remains the standard of care ( 35 ). Alberto Martini et al ( 36 ) reported that neoadjuvant chemotherapy may be an option in patients with UTUC and bone metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…02) and consequently a higher postoperative eGFR ( + 10.97 mL/min/1.73m 2 ; 95%CI 2.97 -18.98, P = .007). 8 However, in cases with pre-operative hydronephrosis and impaired renal function no differences were found between SU and RNU in terms of post-operative eGFR. 9 In line with these results, in this study including patients older than 75 years of age with a pre-operative impaired renal function (mean pre-operative eGFR 52.6 ± 18.5 mL/min/1.73m 2 ), we did not found any significant post-operative variation of renal function in the two groups.…”
Section: Discussionmentioning
confidence: 91%
“…In the NCCN guideline, low-risk or favorable criteria included papillary variant, unifocal, low-grade tumor, size <1.5 cm, and no invasive features in the cross-sectional imaging. A previous study showed that KSS for low-risk UTUCs could reduce morbidity rates, such as loss of kidney function, with oncology outcomes comparable to RNU [6][7][8] . The guidelines of EAU and NCCN recommended management as an option for low-risk and localized UTUCs.…”
Section: Discussionmentioning
confidence: 99%